Steroid treatment resolves acute respiratory failure in patient transferred for ECMO - Körner, Michael M.; Tepolt, Francis; Brehm, Christoph; Bressler, Sonja; Zeriouh, Mohamad; Soleimani, Behzad; Ruhparwar, Arjang; Pae, Walter E.; Loebe, Matthias; Ghodsizad, Ali (The international journal of artificial organs, 2015)
Space-consuming mediastinal tumors can create respiratory failure. We are reporting on a case of mediastinal lymphoma, which created respiratory failure in our patient. IV steroid therapy was used in our patient, who presented with end-stage respiratory failure.